Le regard attractionnel: entre opacité du médium et immersion du spectateur (Cinéma & Cie. Film and Media Studies Journal, 2013)
In a context in which film attraction tends to co-exist with narration, this article examines how filming in natural settings puts into questions the singular and characteristic "method" of the Pathé firm. The authors analyse the transition between studio shooting and outdoor sets by focusing on three animated views and their descriptions in Pathé's catalogues which suggest a hybridization of "scènes en plein air" and "scènes comiques:" "Odyssée d'un paysan à Paris" (1905), "Aux bains de mer" (1906) and" Les Alpes par le télescope" (1906). This article suggests that the transformation of shooting modalities invites reflection on involvement and nature of the spectator's gaze; simultaneously spectators in a cinema as well as background actors/spectators of the film. This demonstration will be accomplished by way of the disjunction between the catalogue descriptions and the views themselves; it will be argued that these major differences direct the spectator's reading of the view, raising the implications of the transition for the spectator.